Characteristics of heavy metals in surface water and assessment of water environment quality in the upper reaches of the Yellow River in recent 10 years. Issue 1 (November 2020) - Cheng, Huibo; Yang, Fan
Abstract: With the rapid development of economy, the load-bearing pressure of ecological environment is increasing, and human activities have brought tremendous challenges to surface water. In this paper, the surface water of 17 cities and counties in the upstream watershed of the reservoir in the source area of the Yellow River was taken as the research object. Based on the monitoring of the surface water quality section of the ecological transfer payment work in the national key ecological functional areas, surface water samples were collected quarterly from 2009 to 2018. Six heavy metal elements (cadmium, mercury, hexavalent chromium, lead, arsenic and copper) in surface water were analyzed in laboratory, and ArcGIS Kriging spatial interpolation method was used to study the spatial distribution characteristics of heavy metals in surface water in the upstream basin of the reservoir in the source area of the Yellow River. Meanwhile, the maximum membership degree method was used to evaluate the quality of water environment. The results showed that the spatial distribution of cadmium, mercury, hexavalent chromium, lead, arsenic and copper in the upstream of the reservoir in the source area of the Yellow River presented a dynamic change, and the high value of cadmium concentration appeared in the northeastern region of the evaluation area as a whole, showing a planar and strip distribution characteristics; the concentration values of mercury in the southwestern region of Maqu County and Luqu County were the highest, and in each county of the northeastern region were relatively lower. In the past 10 years, the average concentration of heavy metals in lead was 0.004 27 mg/L, and that in mercury was 0.000 4 mg/L. According to the maximum membership principle, the environmental quality of heavy metals in surface water in the upstream basin of the reservoir in the source area of the Yellow River in recent 10 years was superior.